Solitary confinement effects, practices, and pathways toward reform - Lobel, Jules; Smith, Peter Scharff 1971- (New York, New York Oxford University Press, 2020)
The use of solitary confinement in prisons became common with the rise of the modern penitentiary during the first half of the nineteenth century and his since remained a feature of many prison systems all over the world. Solitary confinement is used for a panoply of different reasons although research tells us that these practices have widespread negative health effects. Besides the death penalty, it is arguably the most punitive and dangerous intervention available to state authorities in democratic nations. Nevertheless, in the United States there are currently an estimated 80,000 to 100,000 prisoners in small cells for more than 22 hours per day with little or no social contact and no physical contact visits with family or friends. Even in Scandinavia, thousands of prisoners are placed in solitary confinement every year and with an alarming frequency. These facts have spawned international interest in this topic and a growing international reform movement, which includes researchers, litigators, and human rights defenders as well as prison staff and prisoners. This book is the first to take a broad international comparative approach and to apply an interdisciplinary lens to this subject. In this volume neuroscientists, high-level prison officials, social and political scientists, medical doctors, lawyers, and former prisoners and their families from different countries will address the effects and practices of prolonged solitary confinement and the movement for its reform and abolition"--
Includes bibliographical references and index.
Keywords: Prisons. -- Electronic books; Solitary confinement